The Effect of Product Quality, Service Quality, Customer Satisfaction on Customer Loyalty - Nurul Fitrianis Naini; Sugeng Santoso; Tanti Stevany Andriani; Unique Gita Claudia; Nurfadillah Nurfadillah (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2022)
Pujasera Melawai is one area in implementing the DKI Jakarta tourism office program. There are many traditional cuisine menus to choose from, one of which is Restaurant XYZ. This study determines the effect of the product, service quality, & customer satisfaction on customer loyalty in Restaurant XYZ. This study was based on quantitative methods with data collection using a questionnaire by accidental sampling and qualitative method by interviewing the owner of Restaurant XYZ. Quantitative data was taken by anyone who met the purchase requirements at least two times at Restaurant XYZ. The sample was 100 respondents that were analyzed by regression logistics. Based on the questionnaire result and interview with customers and key informants, the three indicators of product and service quality most influential to customer satisfaction and loyalty are response accuracy, product uniqueness, and employees' attention that makes customers happy and want to return restaurant. Based on the results, customer loyalty has a probability of 76.8 percent affected which product quality and customer satisfaction, service quality affects customer loyalty in Restaurant XYZ.